Leucine-protein supplemented recovery feeding enhances subsequent cycling performance in well-trained men - Thomson, J. S.; Ali, A.; Rowlands, D. S. (Applied Physiology, Nutrition, and Metabolism, 2011)
The purpose of this study was to determine whether a practical leucine-protein, high-carbohydrate postexercise feeding regimen could improve recovery, as measured by subsequent cycling performance and mechanistic markers, relative to control feeding. In a crossover, 10 male cyclists performed 2- to 2.5-h interval training bouts on 3 consecutive evenings, ingesting either leucine-protein, high-carbohydrate nutrition (0.1/0.4/1.2/0.2 g/kg.h; leucine, protein, carbohydrate, fat, respectively) or isocaloric control (0.06/1.6/0.2 g/kg·h; protein, carbohydrate, fat, respectively) nutrition for 1.5 h postexercise. Throughout the experimental period diet was controlled, energy and macronutrient intake balanced, and protein intake clamped at 1.6 g/kg·day. The alternate supplement was provided the next morning, thereby isolating the postexercise nutrition effect. Following 39 h of recovery, cyclists performed a repeat-sprint performance test. Postexercise leucine-protein ingestion improved mean sprint power by 2.5% (99% confidence limit, ±2.6%; p = 0.013) and reduced perceived overall tiredness during the sprints by 13% (90% confidence limit, ±9.2%), but perceptions of leg tiredness and soreness were unaffected. Before exercise, creatine-kinase concentration was lowered by 19% (90% confidence limits, ±18%), but lactate dehydrogenase and pressure-pain threshold were unaltered. There was a small reduction in anger (25% ± 18%), but other moods were unchanged. Plasma leucine (3-fold) and essential amino acid (47%) concentrations were elevated postexercise. Net nitrogen balance trended mildly negative in both conditions (mean ± SD: leucine-protein, -20 ± 46 mg/kg per 24 h; control, -25 ± 36 mg/kg per 24 h). The ingestion of a leucine-protein supplement along with other high-carbohydrate food following intense training on consecutive days enhances subsequent high-intensity endurance performance and may attenuate muscle membrane disruption in well-trained male cyclists.